Pengaruh Tarif Pajak, Keadilan Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Pemerintah Daerah Kota Kupang - Made Denny Oktariyana; Fransiskus Marlon Reu; Olivia Latumahina (Jurnal Inovasi Akuntansi (JIA), 2023)
This research aims to determine the effect of Tariffs, Tax Justice and Tax Sanctions on taxpayer compliance. This research uses a quantitative approach, this research was conducted at the Kupang City Regional Government. The Regional Government of Kupang City has a problem related to the number of motor vehicle tax arrears which is increasing every year, in 2022 it will record arrears of 114,571, namely 44% of the total 258,824 registered vehicles. This is due to a lack of taxpayer awareness which causes regional income revenues to not be absorbed optimally. The sampling method used the incidental sampling method, so that a sample of 100 respondents was obtained. This research data was collected using a questionnaire which was then processed using multiple linear regression analysis tests with the help of SPSS version 22. The results of the research stated that Partial Tax Rates had a positive and significant effect on Motor Vehicle Taxpayer Compliance. Tax rates partially have a positive and significant effect on motor vehicle taxpayer compliance. Tax sanctions partially have a positive and insignificant effect on Motor Vehicle Taxpayer Compliance.